죽은 사람의 마음 이론: 죽은 사람의 마음은 시공간을 초월하는가? - 김의선; 김성호; Kim, Euisun; Kim, Sung-Ho (인지과학, 2018)
Current neuroscience views the mind-body problem from the monistic perspective which claims that the human mind is the result of brain activity and that the mind shuts down when the brain does. However, a considerable number of lay people still believe in the existence of the soul and the afterlife, concepts that are hard to explain from the monistic perspective. This study examines whether lay people think that the mind of the dead is capable of exceeding the physical constraints if they believe that such mind exists. After reading one of three vignettes which describes the state of the protagonist as alive, dead, or brain dead, the participants evaluated the protagonist's general mental capacity and transcendental ability to obtain new information. The participants rated that the dead protagonist had more 'transcendental ability to obtain new information' than the alive one if they evaluated high general mental capacity to the protagonist. In addition, unlike the alive condition, in the dead and the brain dead condition, there was a correlation between the general mind capacity rating and the transcendental ability rating. The results suggest that lay people expect the mind of the alive and the dead to be different, as they believe the latter's general mind capacity connotes transcendental ability. We also found that the participants' religiosity affected their beliefs about the transcendental ability of dead person. 현대 신경과학은 인간의 마음이 신체기관인 뇌 활동의 산물이며, 뇌의 활동이 멈추면 마음의 작용도 함께 정지한다는 심신 일원론을 지지한다. 그러나 상당수의 일반인은 여전히 일원론적 입장으로 설명하기 어려운 마음영속성과 사후세계에 대한 믿음을 갖고 있다. 본 연구에서는 죽은 사람의 마음이 단순히 작동정지하거나 약화된 마음이 아니라, 살아있는 사람의 마음과 구별되는, 시공간의 물리적 제약을 초월하는 마음으로 간주되는지 살펴보았다. 참가자들은 주인공이 교통사고 후 사망하거나, 생존하거나, 또는 뇌사상태가 되는 가상의 시나리오를 읽은 뒤, 각 상태의 주인공이 보유한 '일반적 정신능력'과 '초월적 정보수집 능력' 수준을 평정하였다. 연구 결과, 주인공이 사망한 조건에서는 주인공의 일반적 정신능력이 높다고 평가할수록 초월적 정보수집 능력도 높다고 응답하는 상관관계가 관찰되었으나, 생존 조건에서는 이러한 경향성이 관찰되지 않았다. 이는 죽은 사람과 산 사람에게 기대되는 정신능력의 속성이 서로 달라서, 죽은 사람이 소유한 높은 일반 정신능력은 초월적인 능력을 함축함을 시사한다. 추가적으로, 참가자의 종교적 믿음 또한 사망한 사람의 초월적 정보수집 능력에 대한 태도에 영향을 주는 변인임을 확인하였다.